Association of Serum Triglycerides With Arterial Stiffness in Subjects With Low Levels of Low-Density Lipoprotein Cholesterol - Maenohara, Shigeho; Ide, Kazuki; Yoshifuku, Shiro; Kubozono, Takuro; Miyahara, Hironori; Kawasoe, Shin; Usui, Tomoko; Ohishi, Mitsuru; Kawakami, Koji (Circulation Journal, 2018)
Background: The independent role of serum triglyceride (TG) levels as a cardiovascular risk factor is still not elucidated. We aimed to investigate if the effect of TG on arterial stiffness is influenced by the serum level of low-density lipoprotein cholesterol (LDL-C). Methods and Results: We studied 11,640 subjects who underwent health checkups. They were stratified into 4 groups according to LDL-C level (≤79, 80–119, 120–159, and ≥160 mg/dL). Arterial stiffness was evaluated by brachial-ankle pulse wave velocity (baPWV). In each group, univariate and multivariete logistic regression analyses were performed to investigate the association between high TG (≥150 mg/dL) and high baPWV (>1,400 cm/s). In the univarite analysis, high TG was significantly associated with high baPWV in LDL-C <79 mg/dL (OR, 3.611, 95% CI, 2.475–5.337; P<0.0001) and 80–119 mg/dL (OR, 1.881; 95% CI, 1.602–2.210; P<0.0001), but not in LDL-C 120–159 mg/dL and ≥160 mg/dL. In the multivariate analysis, high TG was significantly associated with high baPWV in LDL-C ≤79 mg/dL (OR, 2.558; 95% CI, 1.348–4.914; P=0.0040) and LDL-C 80–119 mg/dL (OR, 1.677; 95% CI, 1.315–2.140; P<0.0001), but not in LDL-C 120–159 mg/dL and ≥160 mg/dL. Conclusions: High TG and increased arterial stiffness showed an independent relationship in a Japanese general population with LDL-C ≤119 mg/dL. TG-lowering therapy might be an additional therapeutic consideration in these subjects.